Question
upstudy study bank question image url

Factorise the following sqares trinomials (a) \( 3 x^{2}-7 x-6 \) (b) \( 3 x^{2}-5 x+2 \)

Ask by Long Fleming. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

(a) \( 3x^{2} - 7x - 6 = (3x + 2)(x - 3) \) (b) \( 3x^{2} - 5x + 2 = (3x - 2)(x - 1) \)

Solution

Certainly! Let's factorize each of the given quadratic trinomials step by step. ### (a) \( 3x^{2} - 7x - 6 \) **Step 1: Identify coefficients** - \( a = 3 \) - \( b = -7 \) - \( c = -6 \) **Step 2: Multiply \( a \) and \( c \)** - \( a \times c = 3 \times (-6) = -18 \) **Step 3: Find two numbers that multiply to \(-18\) and add to \(-7\)** - The numbers are \(-9\) and \(2\) because: - \(-9 \times 2 = -18\) - \(-9 + 2 = -7\) **Step 4: Rewrite the middle term using these numbers** \[ 3x^{2} - 9x + 2x - 6 \] **Step 5: Factor by grouping** \[ (3x^{2} - 9x) + (2x - 6) = 3x(x - 3) + 2(x - 3) = (3x + 2)(x - 3) \] **Final Factored Form:** \[ (3x + 2)(x - 3) \] --- ### (b) \( 3x^{2} - 5x + 2 \) **Step 1: Identify coefficients** - \( a = 3 \) - \( b = -5 \) - \( c = 2 \) **Step 2: Multiply \( a \) and \( c \)** - \( a \times c = 3 \times 2 = 6 \) **Step 3: Find two numbers that multiply to \(6\) and add to \(-5\)** - The numbers are \(-2\) and \(-3\) because: - \(-2 \times -3 = 6\) - \(-2 + (-3) = -5\) **Step 4: Rewrite the middle term using these numbers** \[ 3x^{2} - 2x - 3x + 2 \] **Step 5: Factor by grouping** \[ (3x^{2} - 2x) + (-3x + 2) = x(3x - 2) -1(3x - 2) = (3x - 2)(x - 1) \] **Final Factored Form:** \[ (3x - 2)(x - 1) \] --- **Summary of Factorized Forms:** - **(a)** \( 3x^{2} - 7x - 6 = (3x + 2)(x - 3) \) - **(b)** \( 3x^{2} - 5x + 2 = (3x - 2)(x - 1) \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To factor the trinomial \( 3x^2 - 7x - 6 \), we look for two numbers that multiply to \( 3 \times -6 = -18 \) and add to \( -7 \). The numbers are \( -9 \) and \( 2 \). Rewriting the middle term gives us \( 3x^2 - 9x + 2x - 6 \). Factoring by grouping, we get \( 3x(x - 3) + 2(x - 3) \), simplifying to \( (3x + 2)(x - 3) \). For \( 3x^2 - 5x + 2 \), we need two numbers that multiply to \( 3 \times 2 = 6 \) and add to \( -5 \). The numbers are \( -3 \) and \( -2 \). This allows us to rewrite as \( 3x^2 - 3x - 2x + 2 \). Factoring by grouping leads to \( 3x(x - 1) - 2(x - 1) \), simplifying to \( (3x - 2)(x - 1) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy